2017
DOI: 10.1155/2017/3960197
|View full text |Cite
|
Sign up to set email alerts
|

circRNA_0046367 Prevents Hepatoxicity of Lipid Peroxidation: An Inhibitory Role against Hepatic Steatosis

Abstract: Hepatic steatosis reflects the miRNA-related pathological disorder with triglyceride accumulation and lipid peroxidation, which leads to nonalcoholic steatohepatitis, liver fibrosis/cirrhosis, and even hepatocellular carcinoma. Circular RNA (circRNA)/miRNA interaction reveals a novel layer of epigenetic regulation, yet the miRNA-targeting circRNA remains uncertain in hepatic steatosis. Here, we uncover circRNA_0046367 to be endogenous modulator of miR-34a that underlies hepatic steatosis. In contrast to its ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 70 publications
1
87
0
Order By: Relevance
“…4, 5). Although several recent studies have reported that circRNAs play an important role in the stage of simple steatosis 9,32,33 , it is the first time the current study demonstrates that circRNA participates in the progression of NASH and circRNA_002581 may serve as a novel therapeutic target for the treatment of NASH.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…4, 5). Although several recent studies have reported that circRNAs play an important role in the stage of simple steatosis 9,32,33 , it is the first time the current study demonstrates that circRNA participates in the progression of NASH and circRNA_002581 may serve as a novel therapeutic target for the treatment of NASH.…”
Section: Discussionmentioning
confidence: 69%
“…For instance, circRNA Cdr1as was reported to regulate insulin transcription and secretion in islet cells via binding to miR-7 and further influence its downstream target mRNAs expression 7 . Nevertheless, current reports on the circRNA in NAFLD have been rarely reported, including the metformininduced changes of the coding transcriptome and noncoding RNAs in NAFLD mice 8 and the prevention of hepatocyte lipid peroxidation and steatosis by cir-cRNA_0046367 9 . Therefore, circRNA function in NAFLD is a novel research arena and calls for further intensive study.…”
Section: Introductionmentioning
confidence: 99%
“…Circ‐S‐7 was demonstrated to participate in gastric cancer by interacting with miR‐7 . In hepatic steatosis cells, restoration of hsa_circ_0046367 reduced miR‐34a‐induced PPARα inhibition . In addition, several studies have examined the circRNA‐miRNA‐mRNA axis in HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…39 In hepatic steatosis cells, restoration of hsa_circ_0046367 reduced miR-34a-induced PPARa inhibition. 40 In addition, several studies have examined the circRNA-miRNA-mRNA axis in HCC cells. Fu et al revealed that hsa_circ_0005986 directly interacted with miR129-5p, thereby regulating the mRNA expression level of Notch1.…”
Section: Discussionmentioning
confidence: 99%
“…23 Guo et al found that circFASN expression is lost during hepatic steatosis, suggesting a circFASN-dependent regulatory system in lipid metabolism. 40 Bioinformatically, miR-33a was recognized as a target of circFASN based on circBase (http://www.circbase.org/) and miRBase (http:// microrna.sanger.ac.uk/) analyses. [41][42][43] Experimentally, dual-luciferase reporter assays provided further verification that circFASN acts as a miR-33a "sponge".…”
Section: Discussionmentioning
confidence: 99%